2017
DOI: 10.1108/ijwhm-03-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Usability evaluation (IEQ survey) in hospital buildings

Abstract: Purpose As hospital operations are undergoing major changes, comprehensive methods are needed for evaluating the indoor environment quality (IEQ) and usability of workspaces in hospital buildings. The purpose of this paper is to present a framework of the characteristics that have an impact on the usability of work environments for hospital renovations, and to use this framework to illustrate the usability evaluation process in the real environment. Design/methodology/approach The usability of workspaces in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 31 publications
(45 reference statements)
0
18
0
Order By: Relevance
“…Hignett and Lu, 2009;Jensø and Haugen, 2005;Mollerup, 2009;Pati et al, 2008), but only a few have taken into account the viewpoint of healthcare personnel (e.g. Haron et al, 2012;Capodaglio, 2014;Aalto et al, 2017). Research reports generally discuss the spaces without specifying the usability characteristics from the viewpoint of different user groups.…”
Section: Usable Environment In Hcfsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hignett and Lu, 2009;Jensø and Haugen, 2005;Mollerup, 2009;Pati et al, 2008), but only a few have taken into account the viewpoint of healthcare personnel (e.g. Haron et al, 2012;Capodaglio, 2014;Aalto et al, 2017). Research reports generally discuss the spaces without specifying the usability characteristics from the viewpoint of different user groups.…”
Section: Usable Environment In Hcfsmentioning
confidence: 99%
“…The efficiency requirements for work processes are important, but they should not be detrimental to the well-being of hospital staff. According to Aalto et al (2017), it is essential to consider which usability characteristics enhance and which hinder the performance of various activities from the viewpoint of employees. Aalto et al (2017) have published a usability framework of hospital buildings (Figure 1).…”
Section: Usable Environment In Hcfsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that the outbreak of a serious infectious disease may increase work stress and affect the health of hospital workers [ 33 , 34 , 35 , 36 ]. As rapid changes in care processes may influence the perception of comfort, assessing the hospital environment is needed when changes occur [ 37 ].…”
Section: Introductionmentioning
confidence: 99%